Teaching ORT messages to millions: the BRAC case - Sarkar, Sukhendra Kumar; Karim, Fazlul (BRAC Research and Evaluation Division (RED), 2020)
This secondary data based paper aimed to familiarise the audiences on BRAC experience in successful interpersonal development communication at grassroots. Starting with some basic conceptual issues of communication the paper focused mainly on the BRAC foregone Oral Therapy Extension Programme (OTEP). Through the OTEP BRAC health workers taught miIIions of rural women the "Seven Points to Remember' on diarrhoea and its home management. The reason for adopting this strategy among the many options was that most of the rural mothers were illiterate and superstitious. Therefore, to dispel wrong traditional beliefs and values of the learners, face-to-face teaching was proved to be instrumental and effective. Prior to launching the national programme BRAC, however, experimented a pilot in its SuIIa project. Based on the pilot experience BRAC developed a concise but comprehensive messages on diarrhoea including homemade therapy for its management. The BRAC trained mobile Oral Rehydration Workers taught at least one woman from each household the "Seven Points to Remember" staying at temporary residences given by the community. 'Different fora such as meetings in schools, madrashas, mosques, bazaars and villages were conducted to raise awareness of the male population. Apart from these, mass media were used to disseminate messages. Another vital forum was meeting with the village doctors to win their support to the programme. However, a two-tier mechanism was in place for quality control viz; i) ongoing monitoring system, and ii) operations research and evaluation. The paper also delineated some tips for the Pesticide Association of Bangladesh so that by capitalising the BRAC experiences it can launch interventions to raise peoples' critical awareness on the entirety of pesticide to prevent environmental hazards .